2022
DOI: 10.1007/s10549-021-06508-w
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and predictive accuracy of anti-mullerian hormone for ovarian function after chemotherapy in premenopausal women with early breast cancer

Abstract: Purpose Accurate diagnosis and prediction of loss of ovarian function after chemotherapy for premenopausal women with early breast cancer (eBC) is important for future fertility and clinical decisions regarding the need for subsequent adjuvant ovarian suppression. We have investigated the value of anti-mullerian hormone (AMH) as serum biomarker for this. Methods AMH was measured in serial blood samples from 206 premenopausal women aged 40–45 years with eBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Dillon et al 29 concluded that AMH0 affected both the level and the speed of recovery of AMH without exploring a specific cut-off point. Anderson et al 30 evaluated BC patients between 40 and 45 years of age and, while emphasizing the validity of post-treatment AMH as a marker for ovarian reserve, showed that AMH0 was a significant predictor of AMH after 30 months. This study mainly focused on the prediction of later ovarian function based on the AMH levels 6 months after treatment, which proved to be an accurate marker in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Dillon et al 29 concluded that AMH0 affected both the level and the speed of recovery of AMH without exploring a specific cut-off point. Anderson et al 30 evaluated BC patients between 40 and 45 years of age and, while emphasizing the validity of post-treatment AMH as a marker for ovarian reserve, showed that AMH0 was a significant predictor of AMH after 30 months. This study mainly focused on the prediction of later ovarian function based on the AMH levels 6 months after treatment, which proved to be an accurate marker in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…There are data demonstrating that the absence of anti-mullerian hormone (AMH) is a reliable predictive indicator for loss of ovarian function in premenopausal women after chemotherapy. 58 Future studies can consider the use of AMH along with traditionally accepted criteria using FSH or menstrual history to diagnosis and predict premature ovarian insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…AFC on the third day of the menstrual cycle also appears to be a reliable marker of ovarian follicle pool (Lutchman Singh et al 2007). Of these markers, AMH seems to be the earliest and most reliable indicator of ovarian aging and reduction in post-chemotherapy ovarian reserve and in predicting the return of menses after chemotherapy for breast cancer (Anderson et al 2006;Chai et al 2014;Anderson et al 2022).…”
Section: Assessment Of Chemotherapy-induced Loss In Ovarian Functionmentioning
confidence: 99%